Pengaruh Penerapan Service Learning Berbasis Flipped Classroom terhadap Kesadaran Metakognitif dan Literasi Sains Siswa - Najmiatul Fajar; Santi Kurnia Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to find out the effect of flipped classroom-based service learning application on metacognitive awareness and science literacy in fungi material class X SMA Negeri 3 Batusangkar. This type of research is quasi experiments with the research design Posttest Only Control Group Design with a sample number of students who participated in this study as many as 66 people. Data collection in this study using metacognitive awareness questionnaire and science literacy essay test after the implementation of service learning model based on flipped classroom. As a result of the study, the average grade of experiments for science literacy tests was 74.11 and 67.86 in the control class, while the average scores for metacognitive awareness of experimental class learners were 73.79 and 66.23 in the control class. In conclusion, flipped classroom-based service learning has an influence on metacognitive awareness and science literacy of learners. Keywords: Flipped Classroom, Metacognitive Awareness of Science Literacy, Service Learning